Therapeutic potential of KLF2-induced exosomal microRNAs in pulmonary hypertension - Sindi, Hebah A.; Russomanno, Giusy; Satta, Sandro; Abdul-Salam, Vahitha B.; Jo, Kyeong Beom; Qazi-Chaudhry, Basma; Ainscough, Alexander J.; Szulcek, Robert; Jan Bogaard, Harm; Morgan, Claire C.; Pullamsetti, Soni S.; Alzaydi, Mai M.; et al. (Nature Communications, 2020)
Pulmonary arterial hypertension (PAH) is a severe disorder of lung vasculature that causes right heart failure. Homoeostatic effects of flow-activated transcription factor Krüppel-like factor 2 (KLF2) are compromised in PAH. Here, we show that KLF2-induced exosomal microRNAs, miR-181a-5p and miR-324-5p act together to attenuate pulmonary vascular remodelling and that their actions are mediated by Notch4 and ETS1 and other key regulators of vascular homoeostasis. Expressions of KLF2, miR-181a-5p and miR-324-5p are reduced, while levels of their target genes are elevated in pre-clinical PAH, idiopathic PAH and heritable PAH with missense p.H288Y KLF2 mutation. Therapeutic supplementation of miR-181a-5p and miR-324-5p reduces proliferative and angiogenic responses in patient-derived cells and attenuates disease progression in PAH mice. This study shows that reduced KLF2 signalling is a common feature of human PAH and highlights the potential therapeutic role of KLF2-regulated exosomal miRNAs in PAH and other diseases associated with vascular remodelling.